The morphology and nutrient content drive the leaf carbon capture and economic trait variations in subtropical bamboo forest - Sun, Jun; Li, Jinlong; Koyama, Kohei; Hu, Dandan; Zhong, Quanlin; Cheng, Dongliang (Frontiers in Plant Science, 2023)
Carbon absorption capability and morphological traits are crucial for plant leaf function performance. Here, we investigated the five bamboos at different elevations to clarify how the leaf trait responds to the elevational gradient, and drive the photosynthetic capacity variations. We selected five bamboo species located along different elevations in Wuyi Mountain, southeastern China. The Standardized Major Axis Regression (SMA) analyses and the Structural Equation Model (SEM) are applied to identify how the bamboo leaf trait, including the ratio of leaf width to length (W/L), leaf mass per area (LMA), photosynthesis rates (Pn), leaf nitrogen, and phosphorus concentration (Leaf N and Leaf P) response to elevation environment, and the driving mechanism of Pn changes. Across the five bamboo species, our results revealed the leaf P of Phyllostachys edulis and Oligostachyum oedogonatum decreased with increasing elevation, but the leaf N, and LMA of Indocalamus tessellatus increased. Besides, the leaf P scaled isometrically with respect to W/L, the leaf N scaled allometrically as the 0.80-power of leaf P, and leaf N and leaf P scaled allometrically to Pn, with the exponents of 0.58 and 0.73, respectively. The SEM result showed altitude, morphological trait (W/L and LMA), and chemical trait (leaf N and leaf P) could together explain the 44% variations of Pn, with a standard total effect value of 70.0%, 38.5%, 23.6% to leaf P, leaf N, and W/L, respectively. The five bamboo species along the different elevational share an isometric scaling relationship between their leaf P and W/L, providing partial support for the general rule and operating between morphological and chemical traits. The scaling relationship between leaf P and W/L is insensitive to elevation and species. Further, the leaf W/L and leaf P as the main trait that affects leaf area and P utilization in growth and thus drives bamboo leaf photosynthetic capacity variations in different elevations.